Tara Gum as a Controlled Delivery System of Fluoride in Toothpaste: In Vitro Enamel Remineralization Study - Nayanna Lana Soares Fernandes; Ingrid Andrade Meira; Vanessa Feitosa Alves; Fabio Correia Sampaio; Andressa Feitosa Bezerra de Oliveira (Association of Support to Oral Health Research (APESB), 2021)
Objective:  To evaluate the remineralizing potential of a hydrocolloid-based, controlled fluoride-releasing system added to dentifrice formulas. Material and Methods: Sixty-five human enamel blocks were prepared and the surface microhardness (SH0) values were determined. The artificial caries lesions were induced and the demineralization surface microhardness (SH1) was evaluated. The blocks were randomly allocated into five groups (n = 13): (1) 100-TGF (100% NaF with Tara gum added); (2) 50-TGF (50% free NaF + 50% NaF with Tara gum added); (3) 100% TG (100% Tara gum without fluoride); (4) 100% NaF (positive control); and (5) placebo (without Tara gum and NaF). The blocks were submitted to 7 days pH cycling and treated with dentifrice slurries twice a day. Finally, surface hardness (SH2) was assessed and the percentage of surface hardness recovery (%SMHR) was calculated. Analysis of variance (ANOVA) followed by Bonferroni test was used for statistical analysis. Results: A positive %SMHR was found in the 100% NaF (5.07) and 50-TGF (0.64) groups, while the 100-TGF (-1.38), 100% TG (-3.88) and placebo (-0.52) did not undergo remineralization. Statistically significant differences were observed between 100% NaF and all the groups except for 50-TGF (p<0.05). Conclusion: The presence of hydrocolloid (Tara gum) promoted minimal remineralization when associated with NaF. In the applied model, Tara gum may have compromised remineralization, preventing free fluoride from acting effectively in the carious lesion.